2016
DOI: 10.1007/s11745-016-4206-1
|View full text |Cite
|
Sign up to set email alerts
|

trans Fatty Acids in Colostrum, Mature Milk and Diet of Lactating Adolescents

Abstract: The purpose of this study was to investigate the trans fatty acids (TFA) content and distribution in colostrum, mature milk, and diet of adolescent mothers, after TFA declaration in food labels became mandatory in Brazil. Participants were healthy adolescents (n 54, 15-19 years, 1-90 days postpartum) practicing exclusive breastfeeding. Milk samples were collected 3 days after delivery (colostrum) and in the third month postpartum (mature milk) by hand expression. The fatty acid composition of the milk samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 55 publications
7
34
1
Order By: Relevance
“…However, higher levels of ALA were observed in mature milk compared to the colostrum and transitional groups, as has also been described by other authors [15].…”
Section: Polyunsaturated Fatty Acids (Pufas)supporting
confidence: 87%
See 2 more Smart Citations
“…However, higher levels of ALA were observed in mature milk compared to the colostrum and transitional groups, as has also been described by other authors [15].…”
Section: Polyunsaturated Fatty Acids (Pufas)supporting
confidence: 87%
“…Oleic acid (C18:1 n-9) constitutes more than 90% of the total MUFAs, finding similar values in human milk groups and infant formulas. This is fundamentally linked to the consumption of olive oil, representing levels greater than 40% [6,15].…”
Section: Monounsaturated Fatty Acids (Mufas)mentioning
confidence: 99%
See 1 more Smart Citation
“…The DHA levels found in HMB in the present study (0.10%) were lower than those reported in studies from other countries: Portugal, 0.43% [ 51 ]; Germany, 0.35% [ 52 ]; Italy, 0.26% [ 53 ]; Hungary, 0.23% [ 54 ]; Taiwan, 0.98% [ 55 ]; Israel and the Netherlands, 0.17% [ 56 , 57 ]; China, 0.30% [ 58 ]; South Korea, 0.67% [ 59 ]; and Spain, 0.21% [ 60 ]. In Brazil, a recent study in Rio de Janeiro reported a DHA content of 0.17% in milk sourced from breastfeeding adolescents [ 61 ]. Nishimura et al (2013) evaluated the fatty acid composition of mature human milk from women residing in Ribeirão Preto/São Paulo (far from the Brazilian coast), and found that the DHA content in human milk was among the lowest reported so far (0.09%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Corroborating our findings, lower levels of DHA, total n -3 PUFA and LCPUFA have been previously reported in Brazilian pregnant adolescents of similar socioeconomic condition using erythrocyte FA profile to assess PUFA status [ 29 ]. Even though we have not directly accessed the participant’s dietary intake, we speculate that this could be related to the lipid composition of maternal diet, as evidence on the dietary pattern of Brazilian pregnant and lactating adolescents suggest relatively high intake of n -6 PUFA, especially LA, and low consumption of n -3 LCPUFA, particularly DHA [ 29 , 30 , 31 ]. In addition, endogenous n -3 conversion of ALA to DHA may be inhibited by high dietary levels of the n -6 precursor LA, since both ALA and LA compete as substrates for ∆-6 desaturase, and this may further enhance the reliance upon maternal dietary intake of preformed DHA to meet fetal demands [ 32 ].…”
Section: Discussionmentioning
confidence: 99%